2003
DOI: 10.1136/bjsm.37.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Tibial shaft fractures in amateur footballers

Abstract: Background:Footballers constitute a unique group of patients with tibial shaft fractures. They tend to have excellent general health and well developed musculature in the leg, and their fractures are generally closed injuries caused by low velocity trauma. However, little has been reported on the outcome after tibial shaft fractures in this group.Objective:To identify patterns of injury, response to treatment, and functional outcome in such a group.Method:Fifty consecutive tibial shaft fractures in adult footb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…The Edinburgh study found that 95.4% were closed injuries and of these 90% were Tscherne type 0 or 1 [4]. Delayed union and non-union were also found to be low both by the Leicester study and Lenehan et al quoted a 2% incidence [7]. The latter simply reflects the 'personality' of the tibial fracture as coined by Nicol in 1964 [8] as well as the low mean age of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…The Edinburgh study found that 95.4% were closed injuries and of these 90% were Tscherne type 0 or 1 [4]. Delayed union and non-union were also found to be low both by the Leicester study and Lenehan et al quoted a 2% incidence [7]. The latter simply reflects the 'personality' of the tibial fracture as coined by Nicol in 1964 [8] as well as the low mean age of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…For the surgically managed cohorts, return rates to the same level of sport ranged from 55% to 100% (mean, 75.4%). 9 , 10 , 14 , 16 , 26 - 29 …”
Section: Resultsmentioning
confidence: 99%
“…For patients managed surgically, the rate for reintervention ranged from 2% to 100% (mean, 33%) (Appendix Table 3, available at http://sph.sagepub.com/content/by/supplemental-data ). 1 - 3 , 9 - 14 , 16 , 26 - 29 For those managed with IM nailing, the rate of reintervention ranged from 2% to 52% (mean, 34%), with noted complications including compartment syndrome (range, 0%-33%), wound infection (range, 0%-10%), deep vein thrombosis (0%-5%), fat embolism (0%-9%), and postoperative knee pain (20%-54%). 2 , 3 , 9 - 11 , 14 , 16 , 26 - 29 For patients managed with ORIF, the rate of reintervention ranged from 0% to 40%, with noted complications including wound infection (0%-4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For almost half of these players it marks the end of competitive sport. 1 Most of these fractures are low energy injuries which are stable in configuration. 2 Hence they tend to be treated non-operatively.…”
mentioning
confidence: 99%